A new transdisciplinary research model to investigate and improve the health of the public. (15th January 2021) - Pineo, Helen; Turnbull, Eleanor R; Davies, Michael; Rowson, Mike; Hayward, Andrew C; Hart, Graham; Johnson, Anne M; Aldridge, Robert W
Summary: Transdisciplinary research approaches are being applied to today's complex health problems, including the climate crisis and widening inequalities. Diverse forms of disciplinary and experiential knowledge are required to understand these challenges and develop workable solutions. We aimed to create an updated model reflective of the strengths and challenges of current transdisciplinary health research that can be a guide for future studies. We searched Medline using terms related to transdisciplinary, health and research. We coded data deductively and inductively using thematic analysis to develop a preliminary model of transdisciplinary research. The model was tested and improved through: (i) a workshop with 27 participants at an international conference in Xiamen, China and (ii) online questionnaire feedback from included study authors. Our revised model recommends the following approach: (i) co-learning, an ongoing phase that recognizes the distributed nature of knowledge generation and learning across partners; (ii) (pre-)development, activities that occur before and during project initiation to establish a shared mission and ways of working; (iii) reflection and refinement to evaluate and improve processes and results, responding to emergent information and priorities as an ongoing phase; (iv) conceptualization to develop goals and the study approach by combining diverse knowledge; (v) investigation to conduct the research; (vi) implementation to use new knowledge to solve societal problems. The model includes linear and cyclical processes that may cycle back to project development. Our new model will support transdisciplinary research teams and their partners by detailing the necessary ingredients to conduct such research and achieve health impact.